Impact of UGT2B7 and ABCC2 genetic polymorphisms on mycophenolic acid metabolism in Chinese renal transplant recipients. (22nd October 2018) - Li, Li-qing; Chen, Di-na; Li, Chuan-jiang; Li, Qing-ping; Chen, Yan; Fang, Ping; Zheng, Ping; Lu, Hui-jie; Ye, De-mei; Wan, Hao-yang; Li, Jie; Li, Liang
Aim: To evaluate genetic variants affecting mycophenolic acid (MPA) metabolism in Chinese renal transplant recipients.Methods: Total 11 SNPs of UGT1A9, UGT1A8, UGT2B7, ABCC2, ABCG2 and SLCO1B3 were genotyped in 408 Chinese renal transplant recipients. Associations between SNPs and MPA concentration/dose ratio (C0 /D) were analyzed using different genetic models. Multivariate linear regression was used to analyze associations between log (C0 /D) and clinical factors. Results: After adjustment by clinical factors, UGT2B7 rs7662029 was associated with log (C0 /D) using a dominant (p = 0.041) and an additive (p = 0.038) model, ABCC2 rs717620 was associated with log (C0 /D) using a recessive model (p = 0.019). Using additive model, SNP–SNP interactions were identified (p = 0.002) between ABCC2 rs717620 and UGT1A9 rs2741049, with interactions (p = 0.002) between ABCC2 rs717620 and UGT1A8 rs1042597. Age, albumin and serum creatinine were associated with log (C0 /D).Conclusion: rs7662029 and rs717620 may affect MPA pharmacokinetics. SNP–SNP interactions and clinical factors may have significant effects on MPA metabolism.